Page Kidney: An Unusual Complication of a Renal Transplant Biopsy. (24th April 2018) - McFadden, Jacob D.; Hawksworth, Jason S.
Abstract : Page kidney, a rare phenomenon whereby external compression of renal parenchyma can induce hypertension, can be caused by subcapsular hematoma following renal transplant biopsy. Surgical intervention is often warranted to salvage the transplant kidney. This is a case report of a patient with acute T-cell-mediated rejection and no other risk factors for postprocedural bleeding that developed Page kidney. The patient had no signs or symptoms for >24 hours from the time of biopsy, underscoring the need for awareness of this rare but potentially catastrophic complication of renal transplant biopsies.